2015
DOI: 10.1128/iai.02128-14
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Are the Determinant of Resistance to and Outcome of Nonlethal Babesia microti Infection in Mice

Abstract: cIn the present study, we examined the contributions of macrophages to the outcome of infection with Babesia microti, the etiological agent of human and rodent babesiosis, in BALB/c mice. Mice were treated with clodronate liposome at different times during the course of B. microti infection in order to deplete the macrophages. Notably, a depletion of host macrophages at the early and acute phases of infection caused a significant elevation of parasitemia associated with remarkable mortality in the mice. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 40 publications
4
28
1
Order By: Relevance
“…Instead intra-erythrocyte parasite death was associated with elevated levels of the anti-inflammatory cytokines IL-10, and G-CSF. Other studies of B. microti infection, like the current study, noted serum IL-10 production but also reported modest elevation of serum pro-inflammatory cytokines including IFN-γ (33, 34), which we did not observe. IL-12p40 was also elevated; this cytokine can form homodimers that may play an antagonistic role in the development of IL-12p70 responses, though this remains unclear.…”
Section: Discussioncontrasting
confidence: 72%
“…Instead intra-erythrocyte parasite death was associated with elevated levels of the anti-inflammatory cytokines IL-10, and G-CSF. Other studies of B. microti infection, like the current study, noted serum IL-10 production but also reported modest elevation of serum pro-inflammatory cytokines including IFN-γ (33, 34), which we did not observe. IL-12p40 was also elevated; this cytokine can form homodimers that may play an antagonistic role in the development of IL-12p70 responses, though this remains unclear.…”
Section: Discussioncontrasting
confidence: 72%
“…The spleen does however play a very important role in the clearance of haemoprotozoal organisms as evidenced by the death of splenectomized rats infected with Plasmodium berghei . Another study, similar in methodology, showed the importance of macrophages during the control of both the acute and resolving infections of Babesia microti in mice . In particular, the specific absence of marginal zone and RP macrophages contributed to the failure to control the parasitaemia in the infected mice …”
Section: Discussionmentioning
confidence: 98%
“…2, 27-28, 30 Most fatal cases of human babesiosis occur in splenectomized individuals, although asplenia does not always result in death or even severe illness. The spleen plays a critical role in protection against Babesia spp.…”
Section: Pathogenesismentioning
confidence: 99%